“Human selfgrounding”: Key problems of communicative-semiotic interpretation of the phenomena of language and laughter - S. V. Alpatov; V. V. Nagornykh (Шаги, 2024)
A review of: Kozintsev, A. G. (2024). Iazyk — real’nost’ — igra — smekh: Antropologicheskie fragmenty [Language — reality — game — laughter: Anthropological fragments]. Izdatel’skii dom IaSK. 368 pp. (In Russian).